2022
DOI: 10.2147/opth.s357099
|View full text |Cite
|
Sign up to set email alerts
|

Rub and Rinse Contact Lenses Before Wearing as a Protective Regimen Against Contact Lens-Related Eye Infections

Abstract: Purpose Data on contact lens (CL) users in Thailand are limited, and previous reports have mainly focused on young populations. This study aims to determine demographic data, hygienic behaviour, and complications related to the usage of CLs in the general population. Methods This was a cross-sectional survey conducted from November 2020 to March 2021 using an anonymous questionnaire. Information on the demographic traits of the participants, characteristics of CL use, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…One study reported that 6% of CL users experienced CL-related eye complications each year [ 3 ], and the number of those affected continuously rose along with the number of CL wearers. In our previous study [ 4 ], we found that nearly 40% of CL wearers had poor CL care compliance. The three most common mistakes were not using CL care solution to clean the storage case, not rubbing and rinsing the lens before storage, and exposing CLs to water during wear.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that 6% of CL users experienced CL-related eye complications each year [ 3 ], and the number of those affected continuously rose along with the number of CL wearers. In our previous study [ 4 ], we found that nearly 40% of CL wearers had poor CL care compliance. The three most common mistakes were not using CL care solution to clean the storage case, not rubbing and rinsing the lens before storage, and exposing CLs to water during wear.…”
Section: Introductionmentioning
confidence: 99%